Charging characterization of a high‐capacity lithium‐sulfur pouch cell for state estimation–an experimental approach - Shateri, Neda; Auger, Daniel J.; Fotouhi, Abbas; Brighton, James (Wiley, 2022)
Lithium-Sulfur (Li-S) battery is a next-generation technology, which is promising for applications that require higher energy density in comparison to the available lithium-ion batteries. Along with the ongoing research on Li-S cell material development and manufacturing to improve this technology, engineers are also working on Li-S battery management systems (BMS). The existing BMS algorithms, which are developed for lithium-ion batteries, are not useable for the Li-S mainly due to its constant voltage plateau during the discharge phase. As a result, the Li-S system has poor observability during discharge, which limits the BMS functionality that can be implemented from discharge information alone, and it is worth considering if information from charging is useful. In this study, the charging behavior of a high-capacity pouch cell is investigated and characterized for the purpose of state estimation in a BMS. Several tests are conducted on prototype Li-S cells at different temperatures and age levels. An online feature extraction method is then used in combination with a classification technique to estimate the cell's states during charging. The proposed charging estimators can provide accurate initialization for state estimation accuracy during discharge by providing good estimates of the post-charging state of charge (ie, around 3%) and capacity after fading (ie, around 2%).
Keywords: characterization; charging; feature extraction; lithium-sulfur battery; state estimation